Income Diversification and Financial Stability of Nepalese Commercial Banks - Bist, Roshani (Apex Journal of Business and Management, 2025)
This study investigates how income diversification affects the financial performance of Nepalese commercial banks. It uses secondary data from 20 banks spanning fiscal years 2014/15 to 2023/24, totaling 200 observations. The study applied descriptive statistics, trend analysis, correlation, and regression to analyze data sourced from Nepal Rastra Bank’s Banking and Financial Statistics, annual supervision reports, and banks’ annual reports. Key variables examined include Return on Assets (ROA) and Return on Equity (ROE) as dependent variables, and Net Interest Income, Fee Income, Foreign Exchange Income, Bank Size, and Leverage Ratio as independent variables. Findings show Standard Chartered Bank Nepal Limited (SCBL) had the highest average ROA of 2.04%, while Prabhu Bank Limited (PBL) had the lowest at 1.02%. Regarding ROE, Rastriya Banijya Bank (RBB) topped with 22.23%, and Lumbini Finance Limited (LFL) recorded the lowest at 9.77%. On average, the banks reported 1.44% ROA and 13.69% ROE. Correlation analysis revealed a negative relationship between overall income diversification, bank size, leverage ratio, and profitability measures. However, regression results highlighted that Fee Income and Bank Size positively impact ROA, while Fee Income, Foreign Exchange Income, and Bank Size positively influence ROE. The study suggests focusing on specific income sources—especially fee-based and foreign exchange income—and bank size to enhance profitability. Policymakers and bank managers should emphasize these areas to improve the financial health of Nepalese commercial banks.